Preparation method of hard carbon negative electrode material for sodium ion battery

By simplifying the process and optimizing the preparation process, using biomass crude material to prepare hard carbon negative electrode materials for sodium ion batteries, solving the problems of low carbon yield and high cost, and achieving efficient and low-cost material preparation.

CN119551673APending Publication Date: 2025-03-04CHANGSHA RES INST OF MINING & METALLURGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411843187.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The problem of low carbon yield and high cost of negative electrode materials of sodium ion batteries.

Method used

采用生物质粗料经过酸液活化处理、预碳化、破碎和高温碳化等步骤制备硬碳负极材料,简化工艺并提高碳收率。

Benefits of technology

It improves the carbon yield and capacity of hard carbon anode materials, reduces the preparation cost, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551673A_ABST
    Figure CN119551673A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium-ion batteries, and discloses a preparation method of a hard carbon negative electrode material for a sodium-ion battery, which comprises the following steps: taking biomass as a raw material, and carrying out coarse grinding, acid treatment activation, pre-carbonization, graphite oxide compounding, fine grinding and high-temperature carbonization to obtain the hard carbon negative electrode material. Biomass is adopted as a raw material, the raw material is subjected to acid liquor activation treatment in advance, the microstructure of the carbon material is adjusted, the disorder degree and the sodium storage performance of the material are improved, meanwhile, the preparation process (activation treatment-pre-carbonization-crushing-high-temperature carbonization) is shortened, the yield is improved, and the preparation cost is further reduced; and large-scale industrial production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries and provides a low-cost preparation method of a hard carbon negative electrode material for a sodium ion battery. Background Art

[0002] Lithium-ion batteries (LIBs) have achieved commercial success due to their high energy density, long cycle performance, and lack of memory effect. However, their cost disadvantages and limited global reserves make it difficult to meet the continued demand for large-scale grid energy storage systems. Sodium-ion batteries (SIBs) have been extensively studied and developed as a replacement for LIBs due to their abundant sodium source and similar performance to lithium-ion batteries, becoming a promising new energy storage application.

[0003] So far, people have made a lot of efforts in the development of high-performance positive electrode materials, but the successful commercialization of sodium-ion batteries mainly depends on the progress of the development of negative electrode materials, and there is not enough research on low-cost negative electrode materials with stable mechanical properties. Unlike graphite negative electrodes, hard carbon is a highly disordered structure. It has become the most promising negative electrode material for sodium-ion batteries due to its high sodium storage capacity, low sodium storage potential and excellent cycle stability. Moreover, the current steps for the industrial preparation of hard carbon materials are generally low-temperature carbonization, crushing, purification, and high-temperature carbonization, and the prepared materials are generally above 300mAg / g. However, the high cost of hard carbon precursors due to relatively high prices or low carbon yields limits its industrialization.

[0004] Therefore, developing new precursors and optimizing preparation technologies, improving carbon yield and reducing costs have become important research directions to achieve industrialization requirements. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the problems of low carbon yield and high cost of negative electrode materials for sodium ion batteries, and to provide a method for preparing a high-capacity hard carbon negative electrode material with high carbon yield and low cost.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps: (1) crushing the biomass coarse material into coarse powder to obtain coarse abrasive material; (2) adding the coarse abrasive material to an acid solution for acid treatment to obtain an activated material; (3) pre-carbonizing the activated material under a protective atmosphere to obtain a pre-carbonized material; (4) crushing the pre-carbonized material into fine powder to obtain a hard carbon precursor material; (5) heating the hard carbon precursor material and the graphite oxide solution to obtain a composite material after washing and drying; (6) Carbonizing the composite material under a protective atmosphere to obtain the hard carbon negative electrode material.

[0007] In the above preparation method, preferably, in step (1), the biomass coarse material is any one or more of bamboo, coconut shell, and straw; and the particle size of the coarse abrasive is 100-500 mesh.

[0008] Preferably, in step (2), the acid solution is a mixed solution of any one or more of hydrochloric acid, sulfuric acid, oxalic acid and acetic acid, and the concentration of the acid solution is 1-3M; the acid treatment specifically comprises the following steps: adding the coarse abrasive material to the acid solution, stirring at 100-300 rpm and 60-80°C for 3-5 hours, with a solid-liquid mass ratio of 1:3-5, washing with water after stirring to obtain a filter cake, and drying at 60-80°C to obtain an activated material. The main components of biomass are cellulose, lignin, hemicellulose and inorganic components, and acid treatment can remove inorganic components and modify organic components in the raw materials. During the acid treatment process, the acid reacts chemically with oxides or sulfur impurities on the surface, thereby improving the purity of the raw materials and providing more active sites. In addition, acid treatment can introduce more CC bonds and C=O groups, increase the interlayer distance, enhance the electrochemical reaction activity, and improve the cycle performance.

[0009] Preferably, in steps (3) and (6), the protective atmosphere is any one or more of nitrogen, argon and helium.

[0010] Preferably, in step (3), the pre-carbonization conditions are: a heating rate of 5-10°C / min, a pre-carbonization temperature of 300-800°C, a holding time of 2-6h, and a pre-carbonization equipment is any one of a tube furnace, a box furnace, and a rotary furnace. After pre-carbonization, the carbon-based structure is further stabilized, which is conducive to the dispersion of the graphite oxide solution on the carbon-based structure.

[0011] Preferably, in step (4), the crushing device is any one of a mechanical ball mill, a turbine pulverizer, and a jet mill, and the particle size D50 of the fine powder is 5-10 μm.

[0012] Preferably, in step (5), the graphite oxide solution is prepared from graphite oxide powder, a leaching agent and a solvent, and the concentration of the graphite oxide powder in the graphite oxide solution is 0.1-3M; the preparation ratio of the pre-carbonized material and the graphite oxide solution is 100g:1-2L.

[0013] Preferably, in step (5), the expansion multiple of the graphite oxide is 0.1-1.0, and the particle size is 100-500 mesh; the leaching agent is any one or more of 0.01-1M ammonia water, sodium carbonate or potassium carbonate and other alkaline solutions; the solvent is any one or more of water, ethanol and isopropanol solution.

[0014] Preferably, in step (5), the heating and compounding conditions are: heating and stirring for 4-8 hours, and the heating temperature is 60-80°C.

[0015] Graphite oxide can form a stable dispersion in an alkaline solution. The pre-carbonized material and the graphite oxide solution are heated, mixed and stirred to make the graphite oxide more easily dispersed on the carbon base. The capillary pressure and adsorption of the surface micropores make the graphite oxide evenly coated on the carbon base surface to obtain a composite material.

[0016] Preferably, in step (6), the carbonization conditions are: a heating rate of 5-10°C / min, a carbonization temperature of 1100-1500°C, a holding time of 2-6h, and the carbonization equipment is any one of a tubular furnace, a box furnace, and a rotary furnace.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The basic process for preparing hard carbon negative electrodes in the prior art is generally pretreatment-precarbonization-crushing-purification-high-temperature carbonization; the present invention is a low-cost preparation method for hard carbon negative electrode materials in sodium ion batteries, which uses biomass as raw material, and adjusts the microstructure of the carbon material by pre-activating the raw material with acid solution, thereby improving the disorder and sodium storage performance of the material, and at the same time shortens the preparation process (activation treatment-precarbonization-crushing-high-temperature carbonization), improves the yield, further reduces the preparation cost, and is conducive to large-scale industrial production.

[0018] 2. In the present invention, the acid solution can not only effectively remove impurities and oxides on the surface of the biomass raw material, but also obtain more active sites due to the acid treatment reaction at a specific concentration; after acid treatment and activation, the composite oxidized graphite is further optimized, which can not only adsorb more oxidized graphite, but also introduce a large number of oxygen-containing functional groups, which can effectively inhibit graphitization and expand the interlayer spacing of microcrystals in the subsequent carbonization process, which is beneficial to Na + Insert storage; in addition, acid treatment can shorten the preparation process and no purification treatment is required. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 TEM image of the hard carbon negative electrode material prepared in Example 1 of the present invention; Figure 2 This is the XRD pattern of the hard carbon negative electrode material prepared in Example 1 of the present invention; Figure 3 This is a Raman image of the hard carbon negative electrode material prepared in Example 1 of the present invention; Figure 4 This is the charge and discharge curve of the hard carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0022] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0023] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0024] Embodiment 1: A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, add 2M hydrochloric acid solution, stir at 200 rpm and 75°C for 3 h, with a solid-liquid mass ratio of 1:3, wash with water and filter to obtain a filter cake, and dry it at 80°C to obtain an activated material; (2) placing the activated material in a crucible and placing it in a tubular furnace for pre-carbonization at a temperature of 500°C for 4 hours at a heating rate of 5°C / min, with nitrogen protective gas introduced throughout the process, and naturally cooling to room temperature to obtain a pre-carbonized material; (3) Grinding the pre-carbonized material with a particle size D50 to 5-10 μm using a ball mill at a speed of 300 rpm for 120 min to obtain a hard carbon precursor material; (4) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M ammonia leaching agent was added to obtain a graphite oxide solution. The pre-hard carbon drive material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (5) The hard carbon composite material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1300°C. The temperature is kept at this temperature for 3 h at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0025] Depend on Figure 1 It can be seen from the TEM image that the surface of the grain is covered with a carbon layer with a thickness of 7.828 nm. Its lattice has an ordered structure and high conductivity. It can provide more active centers and fast sodium ion transmission channels, reduce polarization, and promote the diffusion of sodium ions.

[0026] Depend on Figure 2 The XRD spectrum of the prepared composite hard carbon negative electrode shows two broad peaks at 21° and 42°, corresponding to the (002) and (100) graphite planes, respectively. These diffraction peaks indicate that the carbon material is disordered or amorphous. In addition, no other obvious impurity peaks were found. Figure 3 It can be seen that the peak at 1340 is the D band, that is, the disordered defective graphite structure, and the peak at 1590 is the G band, which is related to the crystalline graphite structure. The results show that hard carbon is a disordered graphitized structure, and the Raman results are consistent with the XRD data.

[0027] Depend on Figure 4 It can be seen that in the first charge and discharge curve of the composite hard carbon negative electrode, the 0.1C discharge capacity can reach 380mAhg -1 , 0.1C charging capacity 344.80 mAhg -1 , the first efficiency is 90.69%, and the hard carbon negative electrode material of composite graphite oxide has higher capacity and first efficiency.

[0028] Embodiment 2: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, add 2M hydrochloric acid solution, stir at 200 rpm and 75°C for 3 h, with a solid-liquid mass ratio of 1:3, wash with water and filter to obtain a filter cake, and dry it at 80°C to obtain an activated material; (2) placing the activated material in a crucible and placing it in a tubular furnace for pre-carbonization at a temperature of 500°C for 4 hours at a heating rate of 5°C / min, with nitrogen protective gas introduced throughout the process, and naturally cooling to room temperature to obtain a pre-carbonized material; (3) Grinding the pre-carbonized material with a ball mill to a particle size D50 of 5-10 μm, at a speed of 300 rpm for 120 min, to obtain a hard carbon precursor material; (4) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M Na2CO3 leaching agent was added to obtain a graphite oxide solution. The hard carbon precursor material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (5) The hard carbon composite material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1300°C. The temperature is kept at this temperature for 3 h at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0029] Embodiment 3: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, add 2M hydrochloric acid solution, stir at 200 rpm and 75°C for 3 h, with a solid-liquid mass ratio of 1:3, wash with water and filter to obtain a filter cake, and dry it at 80°C to obtain an activated material; (2) placing the activated material in a crucible and placing it in a tubular furnace for pre-carbonization at a temperature of 500°C for 4 hours at a heating rate of 5°C / min, with nitrogen protective gas introduced throughout the process, and naturally cooling to room temperature to obtain a pre-carbonized material; (3) Grinding the pre-carbonized material with a ball mill to a particle size D50 of 5-10 μm, at a speed of 300 rpm for 120 min, to obtain a hard carbon precursor material; (4) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M ammonia leaching agent was added to obtain a graphite oxide solution. The hard carbon precursor material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (5) The hard carbon composite material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1200°C. The temperature is kept at this temperature for 3 h at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0030] Embodiment 4: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, add 2M hydrochloric acid solution, stir at 200 rpm and 75°C for 3 h, with a solid-liquid mass ratio of 1:3, wash with water and filter to obtain a filter cake, and dry it at 80°C to obtain an activated material; (2) placing the activated material in a crucible and placing it in a tubular furnace for pre-carbonization at a temperature of 500°C for 4 hours at a heating rate of 5°C / min, with nitrogen protective gas introduced throughout the process, and naturally cooling to room temperature to obtain a pre-carbonized material; (3) Grinding the pre-carbonized material with a ball mill to a particle size D50 of 5-10 μm, at a speed of 300 rpm for 120 min, to obtain a hard carbon precursor material; (4) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M ammonia leaching agent was added to obtain a graphite oxide solution. The pre-carbonized material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (5) The hard carbon composite material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1100°C. The temperature is kept at this temperature for 3 h at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0031] Embodiment 5: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, add 1.5M hydrochloric acid solution, stir at 200rpm and 75℃ for 3h, the solid-liquid mass ratio is 1:3, wash with water and filter to obtain the filter cake, and dry it at 80℃ to obtain the activated material; (2) placing the activated material in a crucible and placing it in a tubular furnace for pre-carbonization at a temperature of 500°C for 4 hours at a heating rate of 5°C / min, with nitrogen protective gas introduced throughout the process, and naturally cooling to room temperature to obtain a pre-carbonized material; (3) Grinding the pre-carbonized material with a particle size D50 to 5-10 μm using a ball mill at a speed of 300 rpm for 120 min to obtain a hard carbon precursor material; (4) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M ammonia leaching agent was added to obtain a graphite oxide solution. The pre-hard carbon drive material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (5) The hard carbon composite material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1300°C. The temperature is kept at this temperature for 3 h at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0032] Embodiment 6: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, add 3M hydrochloric acid solution, stir at 200 rpm and 75°C for 3 h, with a solid-liquid mass ratio of 1:3, wash with water and filter to obtain a filter cake, and dry it at 80°C to obtain an activated material; (2) placing the activated material in a crucible and placing it in a tubular furnace for pre-carbonization at a temperature of 500°C for 4 hours at a heating rate of 5°C / min, with nitrogen protective gas introduced throughout the process, and naturally cooling to room temperature to obtain a pre-carbonized material; (3) Grinding the pre-carbonized material with a particle size D50 to 5-10 μm using a ball mill at a speed of 300 rpm for 120 min to obtain a hard carbon precursor material; (4) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M ammonia leaching agent was added to obtain a graphite oxide solution. The pre-hard carbon drive material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (5) The hard carbon composite material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1300°C. The temperature is kept at this temperature for 3 h at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0033] Embodiment 7: A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, add 0.5M hydrochloric acid solution, stir at 200rpm and 75℃ for 3h, the solid-liquid mass ratio is 1:3, wash with water and filter to obtain a filter cake, and dry it at 80℃ to obtain an activated material; (2) placing the activated material in a crucible and placing it in a tubular furnace for pre-carbonization at a temperature of 500°C for 4 hours at a heating rate of 5°C / min, with nitrogen protective gas introduced throughout the process, and naturally cooling to room temperature to obtain a pre-carbonized material; (3) Grinding the pre-carbonized material with a particle size D50 to 5-10 μm using a ball mill at a speed of 300 rpm for 120 min to obtain a hard carbon precursor material; (4) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M ammonia leaching agent was added to obtain a graphite oxide solution. The pre-hard carbon drive material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (5) The hard carbon composite material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1300°C. The temperature is kept at this temperature for 3 h at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0034] Embodiment 8: A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, add 4M hydrochloric acid solution, stir at 200 rpm and 75°C for 3 h, with a solid-liquid mass ratio of 1:3, wash with water and filter to obtain a filter cake, and dry it at 80°C to obtain an activated material; (2) placing the activated material in a crucible and placing it in a tubular furnace for pre-carbonization at a temperature of 500°C for 4 hours at a heating rate of 5°C / min, with nitrogen protective gas introduced throughout the process, and naturally cooling to room temperature to obtain a pre-carbonized material; (3) Grinding the pre-carbonized material with a particle size D50 to 5-10 μm using a ball mill at a speed of 300 rpm for 120 min to obtain a hard carbon precursor material; (4) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M ammonia leaching agent was added to obtain a graphite oxide solution. The pre-hard carbon drive material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (5) The hard carbon composite material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1300°C. The temperature is kept at this temperature for 3 h at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0035] Comparative Example 1 (not compounded with graphite oxide): A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, add 2M hydrochloric acid solution, stir at 100 rpm and 75°C for 3 h, with a solid-liquid mass ratio of 1:3, wash with water and filter to obtain a filter cake, and dry it at 80°C to obtain an activated material; (2) 40 g of activated material was placed in a crucible and placed in a tubular furnace for pre-carbonization at a temperature of 500 °C for 4 h at a heating rate of 5 °C / min. Nitrogen protective gas was introduced throughout the process and the material was naturally cooled to room temperature to obtain a pre-carbonized material. (3) Grinding the pre-carbonized material with a ball mill to a particle size D50 of 5-10 μm, at a speed of 300 rpm for 120 min, to obtain a hard carbon precursor material; (4) The hard carbon precursor material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1300°C. The temperature is kept at this temperature for 3 hours at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0036] Comparative Example 2 (pre-carbonization followed by acid treatment): A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, take 40g and put it directly into a tubular furnace for pre-carbonization. The pre-carbonization temperature is 500℃, the temperature is kept for 4 hours, the heating rate is 5℃ / min, nitrogen protective gas is introduced throughout the process, and it is naturally cooled to room temperature to obtain pre-carbonized material; (2) Grind the pre-carbonized material with a ball mill to a particle size D50 of 5-10 μm, with a ball milling speed of 300 rpm and a time of 120 min to obtain a fine powder; (3) Add the fine powder to 200 mL of 2M hydrochloric acid solution, heat to 80 °C in an oil bath and stir for 4 h. After stirring, filter and wash repeatedly with deionized water until the pH is about 7, and dry at 80 °C for 12 h to obtain a hard carbon precursor material. (4) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M ammonia leaching agent was added to obtain a graphite oxide solution. The pre-carbonized material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (5) The hard carbon precursor material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1300°C. The temperature is kept at this temperature for 3 h at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0037] Comparative Example 3 (without acid treatment): A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps: (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, take 40g and put it directly into a tubular furnace for pre-carbonization. The pre-carbonization temperature is 500℃, the temperature is kept for 4 hours, the heating rate is 5℃ / min, nitrogen protective gas is introduced throughout the process, and it is naturally cooled to room temperature to obtain pre-carbonized material; (2) Grinding the pre-carbonized material with a ball mill to a particle size D50 of 5-10 μm, at a ball milling speed of 300 rpm for 120 min to obtain a hard carbon precursor material; (4) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M ammonia leaching agent was added to obtain a graphite oxide solution. The pre-hard carbon drive material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (4) The composite material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1300°C. The temperature is kept at this temperature for 3 h at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0038] Comparative Example 4 (without pre-carbonization): (1) Use a crusher to crush the bamboo coarse material into a particle size of 100 mesh, add 2M hydrochloric acid solution, stir at 200 rpm and 75°C for 3 h, with a solid-liquid mass ratio of 1:3, wash with water and filter to obtain a filter cake, and dry it at 80°C to obtain an activated material; (2) Grinding the activated material with a ball mill to a particle size D50 of 5-10 μm at a speed of 300 rpm for 120 min to obtain a hard carbon precursor material; (3) A 0.1M aqueous solution was prepared with 325 mesh graphite oxide powder with an expansion multiple of 0.1, and a 0.1M ammonia leaching agent was added to obtain a graphite oxide solution. The pre-hard carbon drive material and the graphite oxide solution (supernatant) were heated to 75°C in an oil bath at a ratio of 100g:1L and stirred for 4h. After stirring, the mixture was repeatedly washed and filtered with deionized water to obtain a filter cake with a pH of 7.0, which was dried at 60°C to obtain a composite material. (4) The hard carbon composite material is placed in a crucible and put into a tubular furnace for high-temperature carbonization at a temperature of 1300°C. The temperature is kept at this temperature for 3 hours at a heating rate of 5°C / min. Nitrogen protective gas is introduced throughout the process. The material is naturally cooled to room temperature to obtain a hard carbon negative electrode material.

[0039] The hard carbon negative electrode materials prepared in Examples 1-8 and Comparative Examples 1-4 were assembled into batteries, respectively, and their electrochemical properties were tested.

[0040] The specific steps are as follows: The slurry was prepared according to the mass ratio of negative electrode: SP: CMC: SBR = 94: 1.5: 2.0: 2.5; the negative electrode slurry was coated on the copper foil with a scraper of about 100 μm, and vacuum dried at 60 ° C for 8 hours; then the compacted density was 1.0 mg / cm 3 After rolling, the electrodes were cut into 16 mm pieces. After vacuum drying for 4 hours, C2032 button cells were assembled in a glove box. The electrolyte used was Duoduo Reagent Sodium Electrolyte NP005 ether, the diaphragm used was PE-glass fiber-PE three-piece diaphragm, the electrolyte was 200 μl, and after standing for 10 hours, a 0.1C charge and discharge test was carried out in a Blue Electric Battery Test Cabinet.

[0041] In summary, the specific surface area, particle size and interlayer spacing of the negative electrode material and the first discharge specific capacity, first charge and discharge efficiency and carbon yield of the corresponding button battery, the test results are shown in Table 1.

[0042] Table 1: Test results of Examples 1-4 and Comparative Examples 1-6

[0043] Compared with Example 2, which was acid-treated after pre-carbonization, and Example 3, which was not acid-treated, Examples 1 and 5-8 were hard carbon negative electrodes that were first acid-treated and then pre-carbonized, treated with acid solutions of different concentrations, and then doped and coated with graphite oxide for modification. It can be seen that with the increase in acid solution concentration (in the range of 1-3M), more active sites are created, the interlayer spacing is increased, and the capacity is significantly increased, but too high a concentration (4M) may cause more defects due to the violent reaction, affecting the embedding of sodium ions; when the concentration is 2M, the capacity and first efficiency of the modified hard carbon negative electrode are the best. Examples 3-4 are to change the carbonization temperature in Example 1. It can be found that with the increase in carbonization temperature, the degree of graphitization increases, which is conducive to the formation of a closed pore structure, thereby reducing the specific surface area, reducing the SEI film on the surface of the material during the charge and discharge cycle, and significantly improving the capacity and first efficiency. Comparative Examples 1 and 4 are hard carbon negative electrodes without doping and coating of graphite oxide after acid treatment and without pre-carbonization. After doping and coating with graphite oxide, not only the surface oxygen-containing functional groups are introduced to increase the active sites and defects, improve the electron mobility, but also increase the specific surface area, enhance the adsorption of sodium ions, and further improve the capacity and first efficiency of the material. Pre-carbonization can make the structure of carbon materials more orderly and more stable, and further improve the conductivity.

[0044] In general, the present invention uses biomass, which is abundant in nature, as raw material, and greatly reduces the preparation cost of high-performance hard carbon negative electrode through process optimization; simplifies the process synthesis parameters and improves the yield in the carbonization process to achieve the maximum effective utilization of raw materials, while lowering energy consumption and increasing the hard carbon yield.

Claims

1. A method for preparing a hard carbon negative electrode material for a sodium ion battery, characterized in that: The steps include: (1) crushing the biomass coarse material into coarse powder to obtain coarse abrasive material; (2) adding the coarse abrasive material to an acid solution for acid treatment to obtain an activated material; (3) pre-carbonizing the activated material under a protective atmosphere to obtain a pre-carbonized material; (4) crushing the pre-carbonized material into fine powder to obtain a hard carbon precursor material; (5) heating the hard carbon precursor material and the graphite oxide solution to obtain a composite material after washing and drying; (6) Carbonizing the composite material under a protective atmosphere to obtain the hard carbon negative electrode material.

2. The preparation method according to claim 1, characterized in that: In step (1), the biomass coarse material is any one or more of bamboo, coconut shell, and straw; and the particle size of the coarse abrasive is 100-500 mesh.

3. The preparation method according to claim 1, characterized in that: In step (2), the acid solution is a mixed solution of any one or more of hydrochloric acid, sulfuric acid, oxalic acid and acetic acid, and the concentration of the acid solution is 1-3M; the acid treatment specifically comprises the following steps: adding the coarse abrasive material to the acid solution, stirring at 100-300 rpm and 60-80°C for 3-5 hours, with a solid-liquid mass ratio of 1:3-5, washing with water after stirring to obtain a filter cake, and drying at 60-80°C to obtain an activated material.

4. The preparation method according to claim 1, characterized in that: In steps (3) and (6), the protective atmosphere is any one or more of nitrogen, argon and helium.

5. The preparation method according to claim 1, characterized in that: In step (3), the pre-carbonization conditions are: a heating rate of 5-10°C / min, a pre-carbonization temperature of 300-800°C, and a holding time of 2-6h.

6. The preparation method according to claim 1, characterized in that: In step (4), the particle size D50 of the fine powder is 5-10 μm.

7. The preparation method according to claim 1, characterized in that: In step (5), the graphite oxide solution is prepared from graphite oxide powder, a leaching agent and a solvent, and the concentration of the graphite oxide powder in the graphite oxide solution is 0.1-3M; the preparation ratio of the pre-carbonized material and the graphite oxide solution is 100g: 1-2L.

8. The preparation method according to claim 6, characterized in that: In step (5), the expansion multiple of the graphite oxide powder is 0.1-1.0, and the particle size is 100-500 mesh; the leaching agent is any one or more of 0.01-1M ammonia water, sodium carbonate, potassium carbonate and other alkaline solutions; the solvent is any one or more of water, ethanol and isopropanol solution.

9. The preparation method according to claim 1, characterized in that: In step (5), the heating and compounding conditions are: heating and stirring for 1-3 hours, and the heating temperature is 60-80°C.

10. The preparation method according to any one of claims 1 to 9, characterized in that: In step (6), the carbonization conditions are: heating rate of 5-10°C / min, carbonization temperature of 1100-1500°C, and holding time of 2-6h.